Conversations with landscape architects and artists: an exploration of the value of creative thinking in landscape architectural design process. - King, Emily (Kansas State University, 2011)
Over time the conventional design process has minimally evolved from Hideo Sasaki’s staged-design process, one of the original models of landscape architectural design process (Murphy 2005, 50; Sasaki 1950, 35). Different types of conventional design process, as it is called in this study, incorporate more stages, devoting more time to each; however, the stages are still completed in an exact order due to the focus on problem solving. The lack of encouragement for personal creative thinking through an individual creative process within the conventional design processes used today is apparent in both the profession and the education of landscape architects today. Because a creative process does not simply solve problems but encourages creative thinking throughout design, the profession would see greater generation of new ideas if landscape architects began to embrace a more creative process, as identified by Graham Wallas in the 1920s (Lawson 2006, 149-150; Herrman 1995; Goswami and Goswami 1999, 43-44). Interviews with highly creative, or avant-garde, landscape architects, such as Thomas Balsley, Claude Cormier, Mikyoung Kim and Peter Walker, and assumedly creative artists helped to provide answers to primary research questions: How does the design process of avant-garde landscape architects compare to the assumedly creative process used by artists? And how can the conventional landscape architectural design process be reframed to incorporate more creative thinking in landscape architectural practice and landscape architectural education? Using a grounded theory approach, in-depth, open-ended interviews were completed with eight subjects. Initial coding themes were based upon broad categories from literature review. Substantial coding and analysis of interviews to find the creative and conventional design processes and characteristics of creativity for each subject resulted in emergent themes and sub-themes from the interviews. Analysis matrices were developed to document commonalities and discrepancies between initial themes from literature review and emergent themes from interviews. Conclusions on findings from initial and emergent themes include:highly creative landscape architects employ non-linear, creative processes throughout design, confidence in personal creativity is imperative to creative thinking, and landscape architectural programs should allow students flexibility and creative license for developing personal design processes.
Keywords: Design Process; Creative Process; Landscape Architects; Artists; Avant-Garde; Education; Art Education (0273); Landscape Architecture (0390)